2015
DOI: 10.1186/s12052-015-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

Predator Escape: An Ecologically Realistic Scenario for the Evolutionary Origins of Multicellularity

Abstract: The origin of multicellularity was transformative for life on earth, allowing for the evolution of the large, complex organisms we see today. Despite its clear importance, the evolution of multicellularity remains a challenging topic to teach, especially at the high school level. Here we present a quick (one or two 50-min sessions) and easy laboratory in which students experimentally examine the hypothesis that small-mouthed predators can select for multicellularity. Students first observe rotifers and yeast (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…Overall, these findings suggest that environmental stress could play a major role in the maintenance, or possibly even the emergence of multicellularity in other species, such as social amoebae (Gregor, Fujimoto, Masaki, & Sawai, ). These findings corroborate the protective role that clumping or other forms of multicellularity provide against predation (Brunke et al, ; Pentz et al, ) and environmental stress (Smukalla et al, ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Overall, these findings suggest that environmental stress could play a major role in the maintenance, or possibly even the emergence of multicellularity in other species, such as social amoebae (Gregor, Fujimoto, Masaki, & Sawai, ). These findings corroborate the protective role that clumping or other forms of multicellularity provide against predation (Brunke et al, ; Pentz et al, ) and environmental stress (Smukalla et al, ).…”
Section: Discussionsupporting
confidence: 77%
“…For example, cooperating "wrinkly spreader" Pseudomonas fluorescens bacteria form multicellular mats on the surface of liquids which improves access to oxygen, but noncontributing unicellular cheats regularly arise and cause colony collapse, subsequently acting as propagules (Hammerschmid, Rose, Kerr, & Rainey, 2014). More broadly, multicellularity may provide the benefits of dispersal in sparse nutrient conditions (Kuzdzal-Fick, Foster, Queller, & Strassmann, 2007;Smith, Queller, & Strassmann, 2014), stress resistance (Smukalla et al, 2008), nutrient acquisition (Koschwanez, Foster, & Murray, 2011), and predator protection (Pentz, Limberg, Beermann, & Ratcliff, 2015). Implicitly, unicellularity is disadvantageous in such conditions-yet it improves growth without stress (Smukalla et al, 2008).…”
mentioning
confidence: 99%
“…Overall, these findings suggest that environmental stress could play a major role in the maintenance, or possibly even the emergence of multicellularity in other species, such as social amoebae (Gregor et al 2010). These findings corroborate the protective role that clumping or other forms of multicellularity provide against predation (Brunke et al 2014;Pentz et al 2015) and environmental stress (Smukalla et al 2008).…”
Section: Discussionsupporting
confidence: 68%
“…Addressing this problem requires charting the environmentdependent downsides and benefits of unicellularity versus multicellularity. For example, multicellularity benefits dispersal in sparse nutrient conditions (Kuzdzal-Fick et al 2007;Smith et al 2014), stress resistance (Smukalla et al 2008), nutrient acquisition (Koschwanez et al 2011) and predator protection (Pentz et al 2015). Implicitly, unicellularity is disadvantageous in such conditions -yet it improves growth without stress (Smukalla et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…There have been at least 25 independent origins of multicellularity across the tree of life, with green plants having multiple instances of gains and secondary losses (Grosberg and Strathmann, 2007). "Predation escape" has been regarded as the driving force for multicellular group formation (Pentz et al, 2015). Many studies have reported the advantages of becoming multicellular and large in avoiding predation (reviewed in Grosberg and Strathmann, 2007), including recent studies in various algae, such as Chlorella spp.…”
mentioning
confidence: 99%